2006
DOI: 10.1203/01.pdr.0000214974.55049.f1
|View full text |Cite
|
Sign up to set email alerts
|

Liver Hepcidin and Stainable Iron Expression in Biliary Atresia

Abstract: Hepcidin is a proposed mammalian host defense peptide that was identified on the basis of its antimicrobial activity, but it was later shown to be a crucial regulator of iron homeostasis and a mediator of the anemia of chronic inflammation. Hepcidin and stainable iron expression in biliary atresia (BA) were investigated in this study. Fresh liver tissues were obtained from 10 patients in the early stage of BA when they underwent Kasai's procedure, 9 in the late stage of BA when they received liver transplantat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 32 publications
5
13
0
Order By: Relevance
“…The liver mean hepcidin mRNA expression was 420-fold less in PBC than in normal control (P ¼ 0.01) (Figure 1), which was consistent with our previous report 11 that hepcidin mRNA expression decreased significantly in cholestatic cirrhosis of BA than that in normal child control. Meanwhile, the liver hepcidin mRNA expressions of HBV, HCV and alcohol-induced non-cholestatic cirrhosis showed no significant difference from the normal control (P ¼ 0.12, 0.13 and 0.29 respectively).…”
Section: Hepcidin Expression Is Significantly Downregulated In Cholessupporting
confidence: 91%
See 1 more Smart Citation
“…The liver mean hepcidin mRNA expression was 420-fold less in PBC than in normal control (P ¼ 0.01) (Figure 1), which was consistent with our previous report 11 that hepcidin mRNA expression decreased significantly in cholestatic cirrhosis of BA than that in normal child control. Meanwhile, the liver hepcidin mRNA expressions of HBV, HCV and alcohol-induced non-cholestatic cirrhosis showed no significant difference from the normal control (P ¼ 0.12, 0.13 and 0.29 respectively).…”
Section: Hepcidin Expression Is Significantly Downregulated In Cholessupporting
confidence: 91%
“…In our previous study, hepatic expression of hepcidin decreased remarkably in the cirrhotic liver due to BA 11 However, in the study of Aoki et al 12 liver hepcidin mRNA correlates only with iron stores, but not inflammation and viral genotype in patients with chronic hepatitis C. In addition, Bergmann et al 13 also showed that levels of hepcidin mRNA did not differ between the controls and cirrhotic livers. On the contrary, a significant decrease in serum prohepcidin was observed in patients with liver cirrhosis compared with healthy individuals, which was most prominent in patients with hepatitis C virus and alcohol-related liver cirrhosis.…”
mentioning
confidence: 72%
“…Obstructive jaundice (OJ) increases the risk of liver injury and sepsis, leading to increased mortality [6,7,[11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…The state of cholestasis in various previous studies in animals and humans raises the stress associated with the induction of inflammatory cytokines and IL-6 [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation